Peer Education Tentang Pemeliharaan Kesehatan Gigi Dan Pemeriksaan Kebersihan Gigi Pada Siswa/I Kelas Iv Sdn 040446 Kabanjahe - Nelly Katharina Manurung; Ngena Ria; Susy Adrianelly Simaremare (Poltekkes Kemenkes Aceh, 2026)
ABSTRACTDental caries remains a major health problem in almost all countries, affecting 60-90% ofschool-age children. The 2018 Basic Health Research (Riskesdas) showed that dental cariesprevalence in Indonesia reached 88.8%. Caries can cause pain, discomfort, premature toothloss, and impaired chewing and speech, negatively impacting children's quality of life.Lack of knowledge about tooth brushing is a contributing factor to dental health problemsin children, therefore education is essential. This education can be delivered through peereducation. This community service activity aims to: train students as a peer group to provideeducation, assess students' knowledge before and after the education, and conduct dentaland oral hygiene checks on students at SD Negeri 040446 Kabanjahe. This peer educationactivity demonstrated positive results. After the education, the majority (90%) of students'knowledge level was in the good category. Their dental and oral hygiene improved, asevidenced by an OHIS score of ≤ 1.2, reaching 87.5% (in the good category).Keywords: Peer Education, Dental Health Maintenance, Dental Hygiene